High-anti-crack conical cement pole and modified preparation process thereof
By using a multi-stage composite liquid admixture group and controlled centrifugal molding, two heating and heat preservation processes, and magnesium fluorosilicate aqueous solution spraying, the problems of difficult control of the liquid admixture addition state and uneven inner wall treatment in the preparation of conical cement poles were solved, thus improving the workability and crack resistance.
Patent Information
- Application Number
- CN202611324104.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-11-03
AI Technical Summary
In the existing process of preparing conical cement poles, it is difficult to control the addition state of liquid phase admixtures, it is not easy to maintain the pole wall thickness and continuous slurry layer during centrifugal molding, and the connection between steam curing and inner wall spraying is insufficient, resulting in difficulty in achieving a balance between workability, demolding performance and inner wall crack resistance.
By using a separate storage type composite liquid phase admixture group, and controlling the order of addition and temperature of the liquid phase components, combined with centrifugal molding, two heating and heat preservation, and spraying treatment with magnesium fluorosilicate aqueous solution, a uniform concrete structure and inner wall reaction layer are formed, ensuring demolding strength and crack resistance.
This achieves uniform concrete distribution and the formation of a continuous, rich mortar layer, reducing water absorption and cracking risk on the inner wall of the rod, and improving construction performance and demolding effect.
Smart Images

Figure CN123026413A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tapered cement pole technology, specifically to a high crack-resistant tapered cement pole and its modified preparation process. Background Technology
[0002] Conical cement bars are made by mixing ordinary silicate cement, mineral admixtures, aggregates, water-reducing agents, and other admixtures into concrete, which is then poured, centrifuged, and steam-cured. The concrete needs to maintain fluidity with a low total water content and achieve the required strength for demolding after steam curing. In existing preparation processes, multiple liquid admixtures are often directly mixed or added simultaneously. Sodium tripolyphosphate, sodium aluminate, triacetin, and polycarboxylate-based high-performance water-reducing agents can easily interfere with each other before being added to the concrete, making it difficult to control the dispersion state and timing of each component. This, in turn, affects the workability, pouring continuity, and demolding performance of the concrete.
[0003] During the centrifugal molding of conical cement poles, the concrete needs to be redistributed along the axial and circumferential directions of the conical steel mold to form a dense pole wall. Existing centrifugal processes lack coordinated control over the centrifugal acceleration, centrifugation time, and residual slurry discharge at each stage. In the initial stage of high-speed centrifugation, the concrete is prone to rapid positional changes, resulting in uneven distribution of aggregate and slurry, fluctuations in pole wall thickness, exposed aggregate on the inner wall, or inconsistent thickness of the rich slurry layer. Insufficient formation of a continuous rich slurry layer also affects the uniformity of subsequent treatment of the pole's inner wall, limiting the effectiveness of controlling water absorption and cracking on the inner wall.
[0004] Existing tapered cement poles mostly employ single-stage high-temperature steam curing. When the pole body is directly heated from its static temperature to a higher temperature, the heating process at different locations within the pole body is not easily kept consistent, which can increase internal and external temperature differences, moisture migration, and subsequent drying shrinkage. After steam curing, the inner wall of the pole is usually not treated, or it is not controlled in conjunction with the pole body surface temperature, spraying time, and wetting reaction conditions. As a result, it is difficult for the magnesium fluorosilicate aqueous solution to spread evenly on the surface of the continuous rich slurry layer and maintain the reaction time. Therefore, how to coordinate the use of a multi-stage composite liquid phase admixture group, centrifugal molding, continuous rich slurry layer, steam curing, and magnesium fluorosilicate aqueous solution spraying treatment is a problem that needs to be solved in this field. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a high-crack-resistant conical cement rod and its modified preparation process, which solves the problems of difficulty in controlling the addition state of liquid phase admixtures, difficulty in maintaining the rod wall thickness and continuous slurry layer during centrifugal molding, and insufficient connection between steam curing and inner wall spraying treatment, resulting in difficulty in simultaneously achieving construction performance, demolding performance and inner wall crack resistance.
[0006] To address the above problems, the present invention provides the following technical solution:
[0007] This invention provides a high crack-resistant conical cement pole, employing the following technical solution:
[0008] A high crack-resistant conical cement pole comprises the following raw materials in parts by weight:
[0009] Based on a total mass of 100 parts of cementitious material:
[0010] Ordinary Portland cement is 65-80 parts;
[0011] Granulated blast furnace slag powder is 20-35 parts;
[0012] The composition of natural medium sand is 105-126 parts.
[0013] The amount of granite crushed stone is 174-195 parts;
[0014] Sodium tripolyphosphate is 0.05-0.12 parts;
[0015] Sodium aluminate is 0.35-0.75 parts;
[0016] Triacetin is 0.05-0.15 parts;
[0017] The aqueous solution of polycarboxylate-based high-performance water-reducing agent is 0.50-1.00 parts;
[0018] The total water consumption is 28-35 units;
[0019] The polycarboxylate-based high-performance water-reducing agent aqueous solution is a polyether-type polycarboxylate water-reducing agent aqueous solution with a solid content of 39% to 41%.
[0020] The total mass fraction of the ordinary silicate cement and the granulated blast furnace slag powder is 100 parts. The total water consumption includes water used to dissolve the sodium tripolyphosphate and sodium aluminate, to mix the triacetin, and water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution.
[0021] By adopting the above technical solution, the ordinary silicate cement can provide early hydration products, and the granulated blast furnace slag powder can participate in subsequent reactions in an alkaline environment, enabling the cementitious material to maintain demolding strength while possessing the ability to develop strength in later stages. The polycarboxylate-based high-performance water-reducing agent aqueous solution is used to disperse the cementitious material particles, enabling the concrete to maintain the workability required for pouring and centrifugal molding within the total water content range.
[0022] The sodium tripolyphosphate is used to adjust the dispersion state of the cementitious material particles and the early reaction rate. The sodium aluminate is used to supplement the aluminum-containing components that can participate in the early reaction. The triacetin is used to adjust the liquid phase state of the concrete and the early reaction process. By controlling the dosage of the above components and combining them with the aggregate structure formed by the natural medium sand and the granite crushed stone, the fluidity of the concrete, the demolding strength after steam curing, and the later volume stability of the rod can be balanced, while reducing the formation of cracks on the inner wall of the rod.
[0023] Preferably, the inner wall of the high crack-resistant conical cement rod is treated with a magnesium fluorosilicate aqueous solution spray.
[0024] The spraying amount of the magnesium fluorosilicate aqueous solution is 0.08–0.15 kg / m². 2 .
[0025] By adopting the above technical solution, the magnesium fluorosilicate aqueous solution can wet and penetrate the pores of the inner wall surface of the rod, reacting with the alkaline hydration products of the inner wall surface to form insoluble reaction products that fill part of the surface pores. Controlling the spraying amount within the above range allows the magnesium fluorosilicate aqueous solution to continuously cover the inner wall of the rod, reducing water absorption and moisture migration on the inner wall surface, and minimizing the development of cracks in the inner wall during wet-dry changes.
[0026] Preferably, the magnesium fluorosilicate aqueous solution is prepared by dissolving magnesium fluorosilicate hexahydrate in water, and the mass fraction of the magnesium fluorosilicate aqueous solution is 3% to 6%.
[0027] By adopting the above technical solution, the mass fraction of the magnesium fluorosilicate aqueous solution is controlled at 3% to 6%, which enables the magnesium fluorosilicate aqueous solution to have a flow state suitable for spraying and surface penetration, and provides the magnesium fluorosilicate required for the inner wall surface reaction. The mass fraction, combined with the spraying amount, can balance the degree of spray coverage and the effect of the inner wall surface reaction.
[0028] This invention also provides a modified preparation process for a high crack-resistant conical cement rod, comprising the following steps:
[0029] A separate storage type composite liquid phase admixture group is prepared, wherein the separate storage type composite liquid phase admixture group includes a sodium tripolyphosphate solution, a sodium aluminate solution and a triacetin mixture stored separately, wherein the triacetin mixture includes an aqueous solution of a polycarboxylic acid-based high-performance water-reducing agent and triacetin.
[0030] Ordinary silicate cement, granulated blast furnace slag powder, natural medium sand and granite crushed stone are put into a forced concrete mixer for dry mixing, and then the sodium tripolyphosphate solution, the sodium aluminate solution and the triacetin ester mixture are added in sequence and stirred to obtain concrete.
[0031] The reinforcing steel cage is fixed inside the conical steel mold, and the concrete is poured into the conical steel mold.
[0032] The conical steel mold after the concrete pouring is completed is placed on a centrifugal molding machine for centrifugal molding. The quality of the residual slurry discharged during the centrifugal molding process is controlled so that the concrete forms a rod with a continuous slurry-rich inner wall inside the conical steel mold.
[0033] After the conical steel mold has been centrifuged and allowed to stand still, it is sent into a steam curing kiln to raise the highest measured internal temperature of the rod to 40℃~45℃ and keep it at that temperature. Then, the highest measured internal temperature of the rod is raised to 58℃~62℃ and kept at that temperature.
[0034] After steam curing, the temperature is reduced, and the rod is demolded when the surface temperature drops to 35℃~45℃.
[0035] A magnesium fluorosilicate aqueous solution is sprayed onto the inner wall of the rod after demolding. After spraying, both ends of the rod are sealed to allow the magnesium fluorosilicate aqueous solution to react with the surface layer of the inner wall of the rod under moist conditions.
[0036] By adopting the above technical solution, the sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture are prepared and stored separately, which can reduce the change in liquid phase state caused by direct contact between different liquid phase components before they are added to concrete. Adding the sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture in that order ensures that each component is evenly dispersed in the concrete, thus maintaining both the fluidity of the concrete and its early strength after steam curing.
[0037] By controlling centrifugal molding, excess slurry discharge, and the thickness of the continuous slurry layer, a rod with a relatively uniform wall thickness can be formed, providing a continuous inner wall treatment surface for the magnesium fluorosilicate aqueous solution. Employing a two-stage steam curing method with heating and heat preservation allows for control of the internal heating process of the rod and the achievement of the required demolding strength. After demolding, utilizing the residual heat of the rod for inner wall spraying and wetting reaction reduces water absorption and subsequent cracking of the inner wall.
[0038] Preferably, the preparation of the distributed storage composite liquid phase admixture group includes the following steps:
[0039] The water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution is deducted from the total water consumption to obtain the prepared water solution, which is then divided into a first part of water, a second part of water, and a third part of water.
[0040] Sodium tripolyphosphate was added to the first portion of water and stirred until no visible solid particles were found, thus obtaining the sodium tripolyphosphate solution.
[0041] Sodium aluminate was added to the second part of water and stirred until the liquid was uniform to obtain the sodium aluminate solution.
[0042] The aqueous solution of the polycarboxylic acid-based high-performance water-reducing agent was added to the third part of the water and stirred. Then, triacetin was added and stirring was continued to obtain the triacetin mixture.
[0043] The sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture were each placed into a sealed container.
[0044] By adopting the above technical solution, the water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution can be deducted from the total water consumption, thus keeping the actual total water consumption of different batches of concrete within a specified range. Preparing the sodium tripolyphosphate, sodium aluminate, the polycarboxylate-based high-performance water-reducing agent aqueous solution, and triacetin separately avoids direct contact between the sodium tripolyphosphate and sodium aluminate before addition to the concrete, and maintains the homogeneity of the three liquid phases.
[0045] Preferably, the mass ratio of the first part of water, the second part of water, and the third part of water is 55-70:10-20:20-25;
[0046] The temperatures of the first portion of water, the second portion of water, and the third portion of water were all adjusted to 15°C to 30°C before the corresponding components were added.
[0047] The stirring speed during the preparation of the sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture was 200 rpm to 400 rpm.
[0048] The stirring time after the sodium tripolyphosphate is added to the first part of water is 3 min to 5 min;
[0049] The stirring time after adding sodium aluminate to the second part of water is 3 min to 5 min;
[0050] The stirring time after the polycarboxylate-based high-performance water-reducing agent aqueous solution is added to the third part of the water is 1 min to 2 min, and the stirring time after the triacetin is added is 5 min to 10 min;
[0051] The sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture are used for mixing the concrete within 10 to 30 minutes after preparation.
[0052] By adopting the above technical solution and distributing the water according to the above ratio, the appropriate amount of water can be provided for the dissolution of sodium tripolyphosphate and sodium aluminate, as well as for the preparation of the triacetin mixture. Controlling the solution temperature, stirring speed, and stirring time can ensure that the sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture reach a homogeneous state.
[0053] Using the three liquid phases in concrete mixing within 10 to 30 minutes after preparation can reduce the impact of moisture evaporation and temperature changes on the concentration and state of the liquid phases during storage, and improve the consistency of the amount of liquid phase added and the state of concrete mixing between different batches.
[0054] Preferably, before the dry mixing, the temperature of the ordinary silicate cement, the granulated blast furnace slag powder, the natural medium sand and the granite crushed stone is adjusted to 15℃~30℃, and the dry mixing time is 30s~60s;
[0055] After the dry mixing is completed, the sodium tripolyphosphate solution is added and stirred for 30 to 60 seconds. The sodium aluminate solution is added within 20 to 40 seconds, and stirring is continued for 20 to 40 seconds. The triacetin mixture is then added within 20 to 40 seconds, and stirring is continued for 60 seconds. The total mixing time from the start of the dry mixing to the end of the wet mixing is 3 to 5 minutes.
[0056] The operation of pouring the concrete into the conical steel mold is completed within 10 to 30 minutes after the concrete is mixed.
[0057] By adopting the above technical solution, adjusting the temperature of the cementitious material and aggregate to 15℃~30℃ and dry mixing for 30s~60s, the ordinary silicate cement, the granulated blast furnace slag powder, the natural medium sand and the granite crushed stone can be evenly distributed, and the initial temperature of the concrete can be kept stable.
[0058] Adding the three liquid phases in the prescribed order and time can reduce the local concentration difference of sodium aluminate in the concrete and ensure that the polycarboxylate-based high-performance water-reducing agent aqueous solution is evenly dispersed among the cementitious material particles. Pouring the concrete within 10 to 30 minutes after mixing allows the concrete to enter the conical steel mold at a stage where it is ready for pouring, thus providing conditions for subsequent centrifugal molding.
[0059] Preferably, the centrifugal molding process includes, in sequence:
[0060] Centrifuge at a centrifugal acceleration of 3g to 6g for 2 to 4 minutes;
[0061] Centrifuge at a centrifugal acceleration of 10g to 18g for 3 to 5 minutes;
[0062] Centrifuge at a centrifugal acceleration of 25g to 35g for 6 to 10 minutes;
[0063] The mass of the residual slurry discharged during the centrifugal molding process accounts for 1% to 3% of the mass of the concrete poured into the conical steel mold;
[0064] The average thickness of the continuous slurry-rich layer at the axial mid-section of the rod is 2 mm to 5 mm.
[0065] By adopting the above technical solution, a lower centrifugal acceleration is first used to distribute the concrete along the conical steel mold, and then the centrifugal acceleration is gradually increased to rearrange the aggregate and slurry and compact the rod wall. This can reduce the uneven wall thickness caused by the rapid change in the position of the concrete at the beginning of high-speed centrifugation.
[0066] The excess slurry discharge is controlled to 1% to 3% of the mass of the concrete poured into the formwork, and the average thickness of the continuous slurry-rich layer is controlled to 2mm to 5mm. This can discharge some free water and excess slurry, while retaining a continuous inner wall slurry layer, reducing exposed aggregate on the inner wall, and providing a continuous surface for subsequent magnesium fluorosilicate aqueous solution treatment.
[0067] Preferably, before being fed into the steam curing kiln, the centrifuged conical steel mold is allowed to stand at 20℃~30℃ for 0.5h~1.5h.
[0068] The measured maximum internal temperature of the rod was raised to 40℃~45℃ using a heating rate of 8℃ / h~12℃ / h, and then held at that temperature for 1.5h~2.5h.
[0069] The highest measured temperature inside the rod is then raised to 58℃~62℃ using a heating rate of 10℃ / h~15℃ / h, and held for 4h~6h.
[0070] By adopting the above technical solution, the static stopping process allows the centrifugally formed rod to form its initial structure before heating. First, raising the highest measured internal temperature of the rod to 40℃~45℃ and maintaining this temperature allows for early hydration of the rod at a lower temperature and reduces the temperature difference between different locations within the rod.
[0071] Raising the measured maximum temperature inside the rod to 58℃~62℃ and maintaining this temperature promotes further reaction of the cementitious material, allowing the rod to reach the strength required for demolding. Using the measured maximum temperature inside the rod as a control parameter reduces the deviation between the ambient temperature of the steam curing kiln and the actual temperature of the rod, and also reduces drying shrinkage and steam consumption caused by single-stage high-temperature curing.
[0072] Preferably, the cooling rate after the steam curing is 8℃ / h to 15℃ / h;
[0073] When the surface temperature of the rod is 35℃~45℃, the magnesium fluorosilicate aqueous solution is sprayed onto the inner wall of the rod.
[0074] After the spraying is completed, seal both ends of the rod body and allow the magnesium fluorosilicate aqueous solution to react with the inner wall surface of the rod body under humid conditions for 30 to 60 minutes.
[0075] By adopting the above technical solution and using a cooling rate of 8℃ / h to 15℃ / h, the temperature change of the rod after steam curing can be controlled, reducing the temperature difference between the inside and outside of the rod caused by excessively rapid cooling. Spraying the magnesium fluorosilicate aqueous solution when the surface temperature of the rod is 35℃ to 45℃ utilizes the residual heat of the rod to promote the spreading and reaction of the treatment solution on the inner wall surface, while simultaneously reducing rapid evaporation of moisture caused by excessively high temperatures.
[0076] After spraying, seal both ends of the rod and keep it moist for 30 to 60 minutes to reduce water loss from the treatment solution. This allows the magnesium fluorosilicate aqueous solution to remain in continuous contact with the inner wall surface of the rod, reducing water absorption on the inner wall surface and minimizing cracks caused by subsequent moisture changes.
[0077] This invention provides a high-crack-resistant conical cement rod and its modified preparation process. It possesses the following beneficial effects:
[0078] 1. This invention stores sodium tripolyphosphate solution, sodium aluminate solution and triacetin mixture separately, and adds them sequentially to dry-mixed ordinary silicate cement, granulated blast furnace slag powder, natural medium sand and granite crushed stone, so that the three solutions and mixture are evenly dispersed, reducing mutual influence before addition, maintaining the continuity of concrete mixing and pouring, and ensuring that the rod meets the demolding requirements after steam curing.
[0079] 2. This invention uses different centrifugal accelerations to centrifuge and controls the quality of the residual slurry discharged during the centrifugal molding process and the average thickness of the continuous slurry-rich layer at the axial mid-section of the rod. This allows the concrete to be gradually distributed and compacted within the conical steel mold, reducing uneven wall thickness and exposed inner wall aggregate, forming a continuous slurry-rich layer, and providing a continuous surface for the spraying and reaction of magnesium fluorosilicate aqueous solution on the inner wall of the rod.
[0080] 3. This invention raises the measured maximum temperature inside the rod body in two stages and keeps it warm each time. Combined with cooling after steam curing, the magnesium fluorosilicate aqueous solution is sprayed onto the inner wall of the rod body within the surface temperature range. After spraying, the two ends of the rod body are sealed, allowing the magnesium fluorosilicate aqueous solution to react with the surface layer of the inner wall of the rod body under humid conditions. This approach takes into account the rod body demolding, the water absorption of the inner wall of the rod body, and the control of cracks in the inner wall of the rod body. Attached Figure Description
[0081] Figure 1This is a vibration amplitude spectrum diagram of the centrifugal molding stabilization stage of the present invention;
[0082] Figure 2 This is a diagram showing the relationship between the bending moment and the deflection at the loading point of the tapered cement pole of the present invention.
[0083] Figure 3 This is the power spectral density diagram of steam flow fluctuation during the heat preservation stage of the present invention. Detailed Implementation
[0084] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0085] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0086] Unless otherwise specified, the dosage of sodium aluminate, sodium tripolyphosphate, and triacetin is based on the total mass of ordinary silicate cement and granulated blast furnace slag powder, and is calculated according to the actual mass of the raw materials; the dosage of polycarboxylate-based high-performance water-reducing agent aqueous solution is based on the total mass of ordinary silicate cement and granulated blast furnace slag powder, and is calculated according to the actual mass of the aqueous solution; the total water consumption includes the water used for preparing each liquid phase and the water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution; all percentages are mass percentages.
[0087] Ordinary Portland cement, P.O52.5, with a specific surface area of 350–400 m², is used. 2 / kg, with a sulfur trioxide mass fraction of 2.5% to 3.5%.
[0088] Granulated blast furnace slag powder uses S95 grade granulated blast furnace slag powder with a specific surface area of 400-500 m². 2 / kg, moisture content ≤1.0%, 28d activity index ≥95%.
[0089] Sodium aluminate has the CAS number 1302-42-7 and the molecular formula NaAlO2. It is an anhydrous powder product with a NaAlO2 mass fraction ≥90.0%.
[0090] Sodium tripolyphosphate has the CAS number 7758-29-4 and the molecular formula Na5P3O. 10 It uses anhydrous powdered product, Na5P3O 10 Quality score ≥ 94.0%.
[0091] Triacetin has the CAS number 102-76-1 and the molecular formula C9H. 14 O6, purity ≥99.0%, moisture content ≤0.2% by mass.
[0092] The polycarboxylate-based high-performance water-reducing agent aqueous solution uses a polyether-type polycarboxylate water-reducing agent aqueous solution with a solid content of 39% to 41%, a pH value of 6.0 to 8.0, and a water reduction rate of ≥25%.
[0093] Magnesium fluorosilicate is magnesium fluorosilicate hexahydrate, CAS number 18972-56-0, molecular formula MgSiF6·6H2O, purity ≥98.0%.
[0094] The fine aggregate is natural medium sand with a fineness modulus of 2.6 to 2.8 and a mud content of ≤2.0%.
[0095] The coarse aggregate is continuously graded granite crushed stone with a particle size of 5-20mm, a mud content of ≤0.5%, and a needle-like and flaky particle content of ≤8.0%.
[0096] Unless otherwise stated, the centrifugal acceleration in this invention is calculated based on the effective radius of rotation at the axial mid-section of the conical steel mold, and the centrifugal acceleration is expressed as a multiple of the gravitational acceleration g, where g is taken as 9.81 m / s². 2 The rotational speed of the centrifugal molding machine is determined based on the effective rotational radius and the set centrifugal acceleration.
[0097] The highest measured temperature inside the pole was obtained using a temperature sensor installed inside the pole. Temperature measuring points were set along the pole's axial direction and located at the midpoint of the pole's wall thickness. During steam curing, the temperature at each measuring point was continuously collected, and the highest value among the measured values at the same time was taken as the highest measured temperature inside the pole. The heating and heat preservation processes were then controlled based on this highest measured temperature inside the pole.
[0098] The surface temperature of the rod is the measured temperature of the outer surface at the center of the rod's axial direction. Three temperature measurement points are evenly selected circumferentially along the outer surface at the center of the rod's axial direction, and the temperature at each measurement point is measured. The arithmetic mean of the three measurements is taken as the surface temperature of the rod. The demolding time and the time for spraying the magnesium fluorosilicate aqueous solution onto the inner wall of the rod are determined according to the above measurement method.
[0099] Preparation Example 1:
[0100] This preparation example provides a method for preparing a storage-type composite liquid phase admixture group for high crack-resistant conical cement bars, including the following steps:
[0101] Based on a total cementitious material mass of 100 parts, weigh out 0.05 parts sodium tripolyphosphate, 0.35 parts sodium aluminate, 0.05 parts triacetin, and 0.50 parts of a polycarboxylate-based high-performance water-reducing agent aqueous solution, controlling the total water consumption to 28 parts. Calculate the water carried over based on the measured solid content of the polycarboxylate-based high-performance water-reducing agent aqueous solution. Subtract the water carried over by the polycarboxylate-based high-performance water-reducing agent aqueous solution from the total water consumption to obtain the prepared solution water. Divide the prepared solution water into three parts (part 1, part 2, and part 3) according to a mass ratio of 70:10:20.
[0102] Adjust the temperature of the first portion of water to 15°C, add sodium tripolyphosphate, and stir at 200 rpm for 3 minutes until no visible solid particles are visible, thus obtaining a sodium tripolyphosphate solution.
[0103] Adjust the temperature of the second portion of water to 15°C, slowly add sodium aluminate, and stir at 200 rpm for 3 minutes until the liquid is homogeneous to obtain a sodium aluminate solution.
[0104] Adjust the water in the third part to 15°C, add the polycarboxylate-based high-performance water-reducing agent aqueous solution and stir for 1 minute, then add triacetin ester and continue stirring at 200 rpm for 5 minutes to obtain a triacetin ester mixture.
[0105] Sodium tripolyphosphate solution, sodium aluminate solution and triacetin mixture were separately placed into sealed containers and used for concrete mixing within 30 minutes after preparation.
[0106] Preparation Example 2:
[0107] This preparation example provides a method for preparing a storage-type composite liquid phase admixture group for high crack-resistant conical cement bars, including the following steps:
[0108] Based on a total cementitious material mass of 100 parts, weigh out 0.08 parts sodium tripolyphosphate, 0.55 parts sodium aluminate, 0.10 parts triacetin, and 0.75 parts of a polycarboxylate-based high-performance water-reducing agent aqueous solution, controlling the total water consumption to 31.5 parts. Calculate the water carried over based on the measured solid content of the polycarboxylate-based high-performance water-reducing agent aqueous solution. Subtract the water carried over by the polycarboxylate-based high-performance water-reducing agent aqueous solution from the total water consumption to obtain the prepared solution water. Divide the prepared solution water into three parts (part 1, part 2, and part 3) according to a mass ratio of 62.5:15:22.5.
[0109] Adjust the temperature of the first portion of water to 22.5°C, add sodium tripolyphosphate, and stir at 300 rpm for 4 minutes until no visible solid particles are visible, thus obtaining a sodium tripolyphosphate solution.
[0110] Adjust the temperature of the second portion of water to 22.5℃, slowly add sodium aluminate, and stir at 300 rpm for 4 minutes until the liquid is homogeneous to obtain a sodium aluminate solution.
[0111] Adjust the water in the third part to 22.5℃, add the polycarboxylate-based high-performance water-reducing agent aqueous solution and stir for 1.5 min, then add triacetin ester and continue stirring at 300 rpm for 7.5 min to obtain the triacetin ester mixture.
[0112] Sodium tripolyphosphate solution, sodium aluminate solution and triacetin mixture were separately placed into sealed containers and used for concrete mixing within 20 minutes after preparation.
[0113] Preparation Example 3:
[0114] This preparation example provides a method for preparing a storage-type composite liquid phase admixture group for high crack-resistant conical cement bars, including the following steps:
[0115] Based on a total cementitious material mass of 100 parts, weigh out 0.12 parts sodium tripolyphosphate, 0.75 parts sodium aluminate, 0.15 parts triacetin, and 1.00 part of a polycarboxylate-based high-performance water-reducing agent aqueous solution, controlling the total water consumption to 35 parts. Calculate the water carried over based on the measured solid content of the polycarboxylate-based high-performance water-reducing agent aqueous solution. Subtract the water carried over by the polycarboxylate-based high-performance water-reducing agent aqueous solution from the total water consumption to obtain the prepared solution water. Divide the prepared solution water into three parts (first part, second part, and third part) according to a mass ratio of 55:20:25.
[0116] Adjust the temperature of the first portion of water to 30°C, add sodium tripolyphosphate, and stir at 400 rpm for 5 minutes until no visible solid particles are visible, thus obtaining a sodium tripolyphosphate solution.
[0117] Adjust the temperature of the second portion of water to 30°C, slowly add sodium aluminate, and stir at 400 rpm for 5 minutes until the liquid is homogeneous to obtain a sodium aluminate solution.
[0118] Adjust the water in the third part to 30°C, add the polycarboxylate-based high-performance water-reducing agent aqueous solution and stir for 2 minutes, then add triacetin ester and continue stirring at 400 rpm for 10 minutes to obtain the triacetin ester mixture.
[0119] Sodium tripolyphosphate solution, sodium aluminate solution and triacetin mixture were separately placed into sealed containers and used for concrete mixing within 10 minutes after preparation.
[0120] Example 1:
[0121] This embodiment provides a modified preparation process for a high crack-resistant conical cement rod, including the following steps:
[0122] Based on a total mass of 100 parts of cementitious materials, weigh out 80 parts of ordinary Portland cement, 20 parts of granulated blast furnace slag powder, 105 parts of natural medium sand, and 195 parts of granite crushed stone. Use the storage-type composite liquid phase admixture group prepared in Preparation Example 1, with a total water content of 28 parts. Adjust the temperature of ordinary Portland cement, granulated blast furnace slag powder, natural medium sand, and granite crushed stone to 15°C, and put them into a forced concrete mixer for dry mixing for 30 seconds.
[0123] Add sodium tripolyphosphate solution and stir for 30 seconds. Add sodium aluminate solution evenly within 20 seconds and continue stirring for 20 seconds. Add triacetin mixture evenly within 20 seconds and continue stirring for 60 seconds. The total mixing time from the start of dry mixing to the end of wet mixing is 3 minutes.
[0124] The reinforcing steel cage is fixed inside the conical steel mold, and the pouring is completed and the conical steel mold is sealed within 10 minutes after the concrete is mixed.
[0125] The conical steel mold was placed on a centrifugal molding machine and centrifuged for 2 minutes at a centrifugal acceleration of 3g, then for 3 minutes at a centrifugal acceleration of 10g, and then for 6 minutes at a centrifugal acceleration of 25g. During the centrifugation process, the mass of the discharged slurry was controlled to be 1% of the mass of the concrete poured into the mold. After centrifugation, the average thickness of the continuous slurry-rich layer at the axial mid-section of the rod was measured to be 2mm.
[0126] After centrifugation, the conical steel mold was left to stand at 20℃ for 0.5h, and then sent to a steam curing kiln. The highest measured internal temperature of the rod was raised to 40℃ at a heating rate of 8℃ / h and held for 1.5h. Then, the highest measured internal temperature of the rod was raised to 58℃ at a heating rate of 10℃ / h and held for 4h.
[0127] After steam curing, the rod is cooled at a rate of 8℃ / h, and demolded when the surface temperature of the rod drops to 35℃.
[0128] Magnesium fluorosilicate hexahydrate was dissolved in water to prepare a 3% (w / w) magnesium fluorosilicate aqueous solution. This solution was then uniformly sprayed onto the inner wall of the pole at a surface temperature of 35°C, with a spraying amount of 0.08 kg / m². 2 After spraying, seal both ends of the pole and allow the magnesium fluorosilicate aqueous solution to react with the inner wall surface of the pole under humid conditions for 30 minutes. Then, cure the pole in an environment of 20℃ and relative humidity of not less than 90% for 28 days to obtain a high crack-resistant conical cement pole.
[0129] Example 2:
[0130] This embodiment provides a modified preparation process for a high crack-resistant conical cement rod, including the following steps:
[0131] Based on a total mass of 100 parts of cementitious materials, weigh out 72.5 parts of ordinary Portland cement, 27.5 parts of granulated blast furnace slag powder, 115.5 parts of natural medium sand, and 184.5 parts of granite crushed stone. Use the storage-type composite liquid phase admixture group prepared in Preparation Example 2, with a total water content of 31.5 parts. Adjust the temperature of ordinary Portland cement, granulated blast furnace slag powder, natural medium sand, and granite crushed stone to 22.5℃, and put them into a forced concrete mixer for dry mixing for 45 seconds.
[0132] Add sodium tripolyphosphate solution and stir for 45 seconds. Add sodium aluminate solution evenly within 30 seconds and continue stirring for 30 seconds. Add triacetin mixture evenly within 30 seconds and continue stirring for 60 seconds. The total mixing time from the start of dry mixing to the end of wet mixing is 4 minutes.
[0133] The reinforcing steel cage is fixed inside the conical steel mold, and the pouring is completed and the conical steel mold is sealed within 20 minutes after the concrete is mixed.
[0134] The conical steel mold was placed on a centrifugal molding machine and centrifuged for 3 minutes at a centrifugal acceleration of 4.5g, then for 4 minutes at a centrifugal acceleration of 14g, and then for 8 minutes at a centrifugal acceleration of 30g. During the centrifugation process, the mass of the discharged slurry was controlled to be 2% of the mass of the concrete poured into the mold. After centrifugation, the average thickness of the continuous slurry-rich layer at the axial mid-section of the rod was measured to be 3.5mm.
[0135] After centrifugation, the conical steel mold was left to stand at 25℃ for 1 hour, and then sent to a steam curing kiln. The highest measured temperature inside the rod was raised to 42.5℃ at a heating rate of 10℃ / h, and held for 2 hours. Then, the highest measured temperature inside the rod was raised to 60℃ at a heating rate of 12.5℃ / h, and held for 5 hours.
[0136] After steam curing, the rod is cooled at a rate of 12℃ / h, and demolded when the surface temperature of the rod drops to 40℃.
[0137] Magnesium fluorosilicate hexahydrate was dissolved in water to prepare a 4.5% (w / w) magnesium fluorosilicate aqueous solution. This solution was then uniformly sprayed onto the inner wall of the pole at a surface temperature of 40°C, with a spraying amount of 0.115 kg / m². 2 After spraying, seal both ends of the pole and allow the magnesium fluorosilicate aqueous solution to react with the inner wall surface of the pole under humid conditions for 45 minutes. Then, cure the pole in an environment of 20℃ and relative humidity of not less than 90% for 28 days to obtain a high crack-resistant conical cement pole.
[0138] Example 3:
[0139] This embodiment provides a modified preparation process for a high crack-resistant conical cement rod, including the following steps:
[0140] Based on a total mass of 100 parts of cementitious materials, weigh out 65 parts of ordinary Portland cement, 35 parts of granulated blast furnace slag powder, 126 parts of natural medium sand, and 174 parts of granite crushed stone. Use the storage-type composite liquid phase admixture group prepared in Preparation Example 3, with a total water content of 35 parts. Adjust the temperature of ordinary Portland cement, granulated blast furnace slag powder, natural medium sand, and granite crushed stone to 30°C, and put them into a forced concrete mixer for dry mixing for 60 seconds.
[0141] Add sodium tripolyphosphate solution and stir for 60 seconds. Add sodium aluminate solution evenly within 40 seconds and continue stirring for 40 seconds. Add triacetin mixture evenly within 40 seconds and continue stirring for 60 seconds. The total mixing time from the start of dry mixing to the end of wet mixing is 5 minutes.
[0142] The reinforcing steel cage is fixed inside the conical steel mold, and the pouring is completed and the conical steel mold is sealed within 30 minutes after the concrete is mixed.
[0143] The conical steel mold was placed on a centrifugal molding machine and centrifuged for 4 minutes at a centrifugal acceleration of 6g, then for 5 minutes at a centrifugal acceleration of 18g, and then for 10 minutes at a centrifugal acceleration of 35g. During the centrifugation process, the mass of the discharged slurry was controlled to be 3% of the mass of the concrete poured into the mold. After centrifugation, the average thickness of the continuous slurry-rich layer at the axial mid-section of the rod was measured to be 5mm.
[0144] After centrifugation, the conical steel mold was left to stand at 30℃ for 1.5 hours, and then sent to a steam curing kiln. The highest measured internal temperature of the rod was raised to 45℃ at a heating rate of 12℃ / h and held for 2.5 hours. Then, the highest measured internal temperature of the rod was raised to 62℃ at a heating rate of 15℃ / h and held for 6 hours.
[0145] After steam curing, the rod is cooled at a rate of 15℃ / h, and demolded when the surface temperature of the rod drops to 45℃.
[0146] Magnesium fluorosilicate hexahydrate was dissolved in water to prepare a 6% (w / w) magnesium fluorosilicate aqueous solution. This solution was then uniformly sprayed onto the inner wall of the pole at a surface temperature of 45°C, with a spraying amount of 0.15 kg / m². 2 After spraying, seal both ends of the pole and allow the magnesium fluorosilicate aqueous solution to react with the inner wall surface of the pole under humid conditions for 60 minutes. Then, cure the pole in an environment of 20℃ and relative humidity of not less than 90% for 28 days to obtain a high crack-resistant conical cement pole.
[0147] Comparative Example 1:
[0148] Compared with Example 2, the difference is that the cementitious material is composed of 100 parts of ordinary Portland cement, without the addition of granulated blast furnace slag powder, while the other parameters and steps are the same.
[0149] Comparative Example 2:
[0150] Compared with Example 2, the difference is that the amount of sodium aluminate is 0, the amount of water in the second part and the timing of its addition remain unchanged, and the other parameters and steps are the same.
[0151] Comparative Example 3:
[0152] Compared with Example 2, the difference is that the amount of sodium tripolyphosphate is 0, the amount of water in the first part and the timing of its addition remain unchanged, and the other parameters and steps are the same.
[0153] Comparative Example 4:
[0154] Compared with Example 2, the difference is that the amount of triacetin is 0, the amount and timing of addition of water and polycarboxylate-based high-performance water-reducing agent aqueous solution in the third part remain unchanged, and the other parameters and steps are the same.
[0155] Comparative Example 5:
[0156] Compared with Example 2, the difference is that after centrifugation and static curing, the highest measured temperature inside the rod is raised to 75°C at a heating rate of 12.5°C / h, and then kept at 75°C for 5 hours. The two-stage heat preservation at 42.5°C and 60°C is not performed. All other parameters and steps are the same.
[0157] Comparative Example 6:
[0158] Compared with Example 2, the difference is that after demolding, the inner wall of the rod is not sprayed with magnesium fluorosilicate aqueous solution, but directly moisturized and cured in an environment of 20°C and relative humidity of not less than 90% for 28 days. All other parameters and steps are the same.
[0159] Test Example 1:
[0160] Experimental description:
[0161] This test example was used to evaluate the workability, centrifugal running status, formation of the slurry-rich layer, demolding strength, and integrity of the cement rods in Examples 1, 2, and 3. Three batches were prepared independently for each example, with five conical cement rods prepared in each batch, and six cubic specimens with a side length of 150 mm were simultaneously formed.
[0162] Experimental steps:
[0163] Samples were taken immediately after each batch of concrete was mixed. The samples were divided into three parts, and the slump was tested at 0 minutes, 15 minutes and 30 minutes after mixing. The same volume of the mixture was taken to measure the bleeding rate at 30 minutes, and the presence of segregation, clumping and abnormal setting was observed.
[0164] Start timing from the end of concrete mixing, test the slump every 2 minutes, and record the time when the slump first drops below 30mm or the mixture cannot be poured continuously and evenly as the effective workable time.
[0165] A vibration acceleration sensor was fixed at the bearing seat of the large end of the conical steel mold. After the high-speed centrifugal speed stabilized, the vibration signal was continuously collected for 20 seconds at a sampling frequency of 200Hz. After removing the DC component from the vibration signal, a fast Fourier transform was performed to obtain the vibration amplitude spectrum in the range of 0 to 30Hz, and the vibration dominant frequency and the effective value of vibration acceleration were recorded.
[0166] After centrifugation, the discharged residual slurry is collected and weighed, and the proportion of the residual slurry mass to the mass of the concrete poured into the formwork is calculated. One cement rod is selected from each batch, and after curing for 28 days, a ring sample with a width of 100 mm is cut from the middle of the rod's axial direction. Twelve measuring points are evenly set along the circumference to measure the thickness of the continuous slurry-rich layer on the inner wall and the wall thickness of the rod. The average thickness of the slurry-rich layer and the range of wall thickness are calculated respectively.
[0167] The cube specimens were cured under the same steam curing regime as the corresponding cement rods. The compressive strength of the cube specimens was tested simultaneously when the cement rods reached the demolding temperature, and the test results were recorded as the demolding compressive strength.
[0168] Record any sticking, corner chipping, localized peeling, and visible cracks that occur during the demolding process of the cement poles; after demolding, inspect the outer surface of the pole and use an industrial endoscope to inspect the inner wall of the pole. Cement poles without through cracks, obvious honeycombing, continuous exposed aggregate, or large-area surface peeling are counted in the number of poles that meet the appearance requirements. Calculate the complete demolding rate and the appearance qualification rate.
[0169] Experimental data:
[0170] The results of the construction performance tests of each group of concrete mixtures are shown in Table 1, and the results of the centrifugal molding and demolding performance tests of each group of conical cement rods are shown in Table 2.
[0171] Table 1. Test results of the workability of concrete mixtures:
[0172] Group Example 1 Example 2 Example 3 Initial slump / mm 54 69 87 15-minute slump / mm 46 61 75 30-minute slump / mm 35 51 58 30-minute water excretion rate / % 0.42 0.18 0.37 Effective operable time / min 28 37 34
[0173] Table 2. Results of centrifugal molding and demolding performance tests:
[0174] Group Example 1 Example 2 Example 3 Vibration dominant frequency / Hz 4.06 4.44 4.82 <![CDATA[Vibration acceleration RMS value / (m / s 2 )]]> 0.86 0.72 0.93 Residual slurry discharge rate / % 1.08 1.94 2.91 Average thickness of slurry layer / mm 2.1 3.6 4.9 Wall thickness range / mm 3.4 2.6 3.8 Demolding compressive strength / MPa 42.7 47.9 45.8 Complete demolding rate / % 93.3 100.0 93.3 Appearance pass rate / % 93.3 93.3 93.3
[0175] Experimental conclusion:
[0176] Referring to Table 1, Examples 1, 2, and 3 all exhibited workability suitable for pouring after mixing, with a slump of 35–58 mm at 30 minutes and an effective workable time of 28–37 minutes, all covering the corresponding pouring time. The 30-minute bleeding rate for each group was less than 0.5%, and no significant segregation, clumping, or loss of fluidity before pouring was observed during the test. Example 2 showed a slump of 51 mm at 30 minutes, a bleeding rate of 0.18%, and an effective workable time of 37 minutes, indicating that this formulation achieved good coordination between maintaining fluidity and controlling bleeding.
[0177] Referring to Table 2, the residual slurry discharge rates of the three embodiments were 1.08%, 1.94%, and 2.91%, respectively, which are close to the corresponding process settings. A continuous slurry-rich layer was formed in the axial middle of the rod body, with an average thickness of 2.1–4.9 mm. The demolding compressive strength of each group was 42.7–47.9 MPa, and the complete demolding rate was not less than 93.3%, indicating that the multi-stage centrifugation, two-stage steam curing, and subsequent demolding operations could be completed continuously. The wall thickness difference of Example 2 was 2.6 mm, the complete demolding rate was 100.0%, and the appearance qualification rate was 93.3%, indicating relatively good molding uniformity and demolding integrity.
[0178] See attached document Figure 1 The main vibration peaks corresponding to Examples 1, 2, and 3 are located near 4.06Hz, 4.44Hz, and 4.82Hz, respectively, consistent with the main frequencies recorded in Table 2. Outside the main frequencies, each curve only shows low-amplitude harmonic components, and no multiple abnormal peaks with amplitudes close to the main peak appear in the 0–30Hz range. Referring to Table 2, the effective vibration acceleration value of Example 2 is 0.72 m / s². 2 The relatively small wall thickness difference indicates that the mold operates smoothly during centrifugation, and the concrete is evenly distributed along the circumference of the rod. (Attached) Figure 1 The spectral characteristics in the data correspond to the amount of excess slurry discharged, the thickness of the slurry-rich layer, and the demolding results, which can be used to prove that all three embodiments can achieve stable centrifugal molding.
[0179] Test Example 2:
[0180] Experimental description:
[0181] This test example is used to evaluate the later-stage strength, flexural bearing capacity, and internal wall crack resistance of the conical cement rods and concrete specimens from the same batch prepared in Examples 1, 2, 3, and Comparative Examples 1 to 6.
[0182] Six cubic specimens with sides of 150 mm and six conical cement rods were prepared simultaneously for each group. The cubic specimens were used for 28-day and 90-day compressive strength tests, respectively; three conical cement rods were used for 28-day flexural bearing tests, and the other three were used for 90-day internal wall crack inspection. All results were taken as the arithmetic mean of three parallel specimens or three conical cement rods.
[0183] Experimental steps:
[0184] The cubic specimens and the corresponding conical cement rods from the same batch were cured under the same conditions, and their compressive strength was tested at 28 days and 90 days of age, respectively. Three specimens were tested at each age and the average value was taken.
[0185] A bending load test was conducted at 28 days of age. The tapered cement rod was fixed horizontally, and the loading point was set at 0.6m from the tip. The load was applied in stages, and the deflection at the loading point was continuously recorded using a displacement sensor. The bending moment corresponding to the first appearance of a visible crack with a width of not less than 0.02mm was recorded as the cracking bending moment.
[0186] Continue loading until the bending moment reaches 45 kN·m and hold for 5 minutes, measuring the maximum crack width in the tension zone; then continue loading until the bar's load-bearing capacity decreases, recording the maximum bending moment during loading as the ultimate bending moment. Plot the approximate bending moment and deflection at the loading point based on the bending moment and the deflection at the loading point. Figure 2 ;
[0187] At 90 days of age, the inner wall of the rod without bending load was inspected using an industrial endoscope. Cracks with a width of not less than 0.02 mm and a length of not less than 20 mm were counted as visible cracks, and the number of cracks, total crack length, and maximum crack width were recorded.
[0188] Experimental data:
[0189] The test results of compressive strength and bending performance of each group of concrete specimens are shown in Table 3, and the test results of visible cracks on the inner wall of each group of conical cement rods at 90 days of age are shown in Table 4.
[0190] Table 3. Test results of concrete strength and bending performance of tapered cement poles:
[0191] Group 28-day compressive strength / MPa 90-day compressive strength / MPa Cracking moment / (kN·m) Maximum crack width / mm Ultimate bending moment / (kN·m) Example 1 67.4 71.9 35.7 0.18 67.8 Example 2 72.8 77.6 39.4 0.13 74.6 Example 3 70.7 75.2 37.8 0.16 71.9 Comparative Example 1 68.1 69.4 31.9 0.24 65.2 Comparative Example 2 67.0 72.5 34.1 0.21 68.4 Comparative Example 3 68.9 72.7 32.8 0.27 64.7 Comparative Example 4 70.5 74.1 34.9 0.22 67.1 Comparative Example 5 68.5 69.8 30.6 0.29 62.9 Comparative Example 6 72.3 77.0 38.5 0.16 73.8
[0192] Table 4. Inspection results of visible cracks on the inner wall of the conical cement pole within 90 days:
[0193] Group Number of cracks / strips Total crack length / mm Maximum crack width / mm Example 1 3.3 178 0.08 Example 2 1.3 67 0.04 Example 3 2.3 118 0.06 Comparative Example 1 6.3 329 0.13 Comparative Example 2 4.7 254 0.11 Comparative Example 3 7.7 401 0.16 Comparative Example 4 6.7 337 0.14 Comparative Example 5 9.3 482 0.19 Comparative Example 6 3.3 165 0.08
[0194] Experimental conclusion:
[0195] Referring to Table 3, the 28-day and 90-day compressive strengths of Example 2 were 72.8 MPa and 77.6 MPa, respectively; the cracking moment and ultimate bending moment were 39.4 kN·m and 74.6 kN·m, respectively; and the maximum crack width at a bending moment of 45 kN·m was 0.13 mm. Comparative Example 1, without the addition of granulated blast furnace slag powder, showed a slower increase in 90-day strength; Comparative Example 2, without the addition of sodium aluminate, had lower 28-day compressive strength and cracking moment than Example 2, indicating that the combined use of slag powder and sodium aluminate is beneficial for strength development and load-bearing capacity maintenance.
[0196] See attached document Figure 2 In Example 2, the bending moment corresponding to the deflection at the same loading point was higher than that in Comparative Examples 1, 2, 3, and 5 for most of the loading range, and the bearing capacity gradually decreased after reaching the peak bending moment. Comparative Examples 3 and 5 entered the cracking stage at lower bending moments, and their peak bending moments were also lower than those in Example 2. (Appendix) Figure 2 The curve changes in the figure correspond to the cracking moment, maximum crack width, and ultimate bending moment results in Table 3.
[0197] Referring to Table 4, Comparative Examples 3, 4, and 5 showed higher numbers of cracks, total crack length, and maximum crack width at 90 days of age compared to Example 2, indicating that sodium tripolyphosphate, triacetin, and two-stage steam curing all contribute to controlling cracks on the inner wall of the rod. Comparative Example 6 exhibited strength and flexural properties similar to Example 2, but its total inner wall crack length and maximum crack width were higher, suggesting that magnesium fluorosilicate inner wall treatment plays a role in controlling visible cracks in later stages.
[0198] Test Example 3:
[0199] Experimental description:
[0200] This test example is used to evaluate the drying shrinkage and water absorption properties of the conical cement rods and specimens from the same batch prepared in Example 2, Comparative Example 4, Comparative Example 5 and Comparative Example 6, and to compare the steam consumption and steam flow fluctuations during the steam curing process in Example 2 and Comparative Example 5.
[0201] Three prism specimens (100mm × 100mm × 515mm) were prepared for each group, and three conical cement rods were selected for internal wall water absorption testing. Steam curing data were taken as the average of five consecutively produced conical cement rods.
[0202] Experimental steps:
[0203] The initial length of the prism specimen was measured 24 hours after demolding. It was then placed in an environment of 20±2℃ and 60±5% relative humidity. The length change was measured and the drying shrinkage rate was calculated at 28 days and 90 days.
[0204] After the conical cement pole has been cured for 28 days, an inner wall sample is taken from the middle of the pole's axial direction. The non-test surface is sealed, and the test surface is immersed in water for 3 mm. The capillary water absorption is calculated based on the mass change over 24 hours.
[0205] A test area of 100 cm² was fixed on the inner wall at the mid-axis of the rod. 2 A fixed-area water absorption device is used to maintain a 20mm water head for 30 minutes, and the water absorption per unit area of the inner wall is calculated based on the change in water volume.
[0206] During steam curing, instantaneous steam flow and cumulative flow were recorded at 1-minute sampling intervals to calculate the steam consumption of a single conical cement rod. The flow data during the insulation stage were extracted, and after removing the average value and linear trend, the Welch method was used to calculate the power spectral density of steam flow fluctuation.
[0207] Experimental data:
[0208] The results of the drying shrinkage and water absorption performance tests of each group of specimens are shown in Table 5. The steam curing parameters and steam consumption of Example 2 and Comparative Example 5 are shown in Table 6.
[0209] Table 5. Results of drying shrinkage and water absorption performance tests:
[0210] Group <![CDATA[28-day drying shrinkage rate / (×10 -6 )]]> <![CDATA[90-day drying shrinkage rate / (×10 -6 )]]> <![CDATA[24-hour capillary water absorption / (kg / m 2 )]]> <![CDATA[Water absorption per unit area of the inner wall within 30min / (g / m 2 )]]> Example 2 248 286 0.78 141 Comparative Example 4 331 421 1.02 214 Comparative Example 5 409 488 1.27 246 Comparative Example 6 266 318 1.24 312
[0211] Table 6. Steam curing parameters and steam consumption:
[0212] Group Maximum rod body core temperature / ℃ Total steam curing time / hour Steam consumption per unit / kg Example 2 60.4 11.9 148.6 Comparative Example 5 75.8 12.0 186.4
[0213] Experimental conclusion:
[0214] Referring to Table 5, the drying shrinkage rates of Example 2 after 28 days and 90 days were 248 × 10⁻⁶. -6 and 286×10 -6 The results were lower than those of Comparative Example 4 and Comparative Example 5. Comparative Example 4 did not contain triacetin, and Comparative Example 5 used single-stage high-temperature steam curing. Their 90-day drying shrinkage rates were 421 × 10⁻⁶. -6 and 488×10 -6 This indicates that triacetin and two-stage steam curing help control long-term drying shrinkage.
[0215] Referring to Table 5, the 24-hour capillary water absorption and 30-minute water absorption per unit area of the inner wall in Example 2 were 0.78 kg / m². 2 and 141g / m 2 Comparative Example 6, which did not undergo magnesium fluorosilicate inner wall treatment, had a corresponding value of 1.24 kg / m³. 2 and 312g / m 2 This indicates that magnesium fluorosilicate treatment can reduce the water absorption of the inner wall of the rod.
[0216] Refer to Table 6 and Appendix Figure 3 The total steam curing time in Example 2 is similar to that in Comparative Example 5, but the highest core temperature and single-spindle steam consumption in Example 2 are both lower. Figure 3 The results show that Comparative Example 5 was achieved in approximately 0.016 minutes. -1 and 0.052min -1 A higher power spectral peak was observed at the specified location, while the power spectral density in Example 2 was lower within the corresponding frequency range. This result indicates that two-stage steam curing can reduce low-frequency fluctuations in steam flow during the insulation stage and decrease cumulative steam consumption.
[0217] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high crack-resistant conical cement pole, characterized in that, Raw materials comprising the following parts by weight: Based on a total mass of 100 parts of cementitious material: Ordinary Portland cement: 65-80 parts; Granulated blast furnace slag powder: 20-35 parts; Natural medium sand: 105-126 parts; Granite crushed stone: 174-195 parts; Sodium tripolyphosphate: 0.05-0.12 parts; Sodium aluminate: 0.35-0.75 parts; Triacetin: 0.05-0.15 parts; Aqueous solution of polycarboxylate-based high-performance water-reducing agent: 0.50-1.00 parts; Total water consumption: 28-35 units; The polycarboxylate-based high-performance water-reducing agent aqueous solution is a polyether-type polycarboxylate water-reducing agent aqueous solution with a solid content of 39% to 41%. The total mass fraction of the ordinary silicate cement and the granulated blast furnace slag powder is 100 parts. The total water consumption includes water used to dissolve the sodium tripolyphosphate and sodium aluminate, to mix the triacetin, and water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution.
2. The high crack-resistant conical cement pole according to claim 1, characterized in that, The inner wall of the high crack-resistant conical cement rod is treated with magnesium fluorosilicate aqueous solution spraying. The spraying amount of the magnesium fluorosilicate aqueous solution is 0.08–0.15 kg / m². 2 .
3. The high crack-resistant conical cement pole according to claim 2, characterized in that, The magnesium fluorosilicate aqueous solution is prepared by dissolving magnesium fluorosilicate hexahydrate in water, and the mass fraction of the magnesium fluorosilicate aqueous solution is 3% to 6%.
4. A modified preparation process for a high crack-resistant conical cement rod according to any one of claims 1 to 3, characterized in that, Includes the following steps: A separate storage type composite liquid phase admixture group is prepared, wherein the separate storage type composite liquid phase admixture group includes a sodium tripolyphosphate solution, a sodium aluminate solution and a triacetin mixture stored separately, wherein the triacetin mixture includes an aqueous solution of a polycarboxylic acid-based high-performance water-reducing agent and triacetin. Ordinary silicate cement, granulated blast furnace slag powder, natural medium sand and granite crushed stone are put into a forced concrete mixer for dry mixing, and then the sodium tripolyphosphate solution, the sodium aluminate solution and the triacetin ester mixture are added in sequence and stirred to obtain concrete. The reinforcing steel cage is fixed inside the conical steel mold, and the concrete is poured into the conical steel mold. The conical steel mold after the concrete pouring is completed is placed on a centrifugal molding machine for centrifugal molding. The quality of the residual slurry discharged during the centrifugal molding process is controlled so that the concrete forms a rod with a continuous slurry-rich inner wall inside the conical steel mold. After the conical steel mold has been centrifuged and allowed to stand still, it is sent into a steam curing kiln to raise the highest measured internal temperature of the rod to 40℃~45℃ and keep it at that temperature. Then, the highest measured internal temperature of the rod is raised to 58℃~62℃ and kept at that temperature. After steam curing, the temperature is reduced, and the rod is demolded when the surface temperature drops to 35℃~45℃. A magnesium fluorosilicate aqueous solution is sprayed onto the inner wall of the rod after demolding. After spraying, both ends of the rod are sealed to allow the magnesium fluorosilicate aqueous solution to react with the surface layer of the inner wall of the rod under moist conditions.
5. The modified preparation process according to claim 4, characterized in that, The preparation of the distributed composite liquid admixture group includes the following steps: The water introduced by the polycarboxylate-based high-performance water-reducing agent aqueous solution is deducted from the total water consumption to obtain the prepared water solution, which is then divided into a first part of water, a second part of water, and a third part of water. Sodium tripolyphosphate was added to the first portion of water and stirred until no visible solid particles were found, thus obtaining the sodium tripolyphosphate solution. Sodium aluminate was added to the second part of water and stirred until the liquid was homogeneous to obtain the sodium aluminate solution. The aqueous solution of the polycarboxylic acid-based high-performance water-reducing agent was added to the third part of the water and stirred. Then, triacetin was added and stirring was continued to obtain the triacetin mixture. The sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture were each placed into a sealed container.
6. The modified preparation process according to claim 5, characterized in that, The mass ratio of the first portion of water, the second portion of water, and the third portion of water is (55-70):(10-20):(20-25); The temperatures of the first portion of water, the second portion of water, and the third portion of water were all adjusted to 15°C to 30°C before the corresponding components were added. The stirring speed during the preparation of the sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture was 200 rpm to 400 rpm. The stirring time after the sodium tripolyphosphate is added to the first part of water is 3 min to 5 min; The stirring time after adding sodium aluminate to the second part of water is 3 min to 5 min; The stirring time after the polycarboxylate-based high-performance water-reducing agent aqueous solution is added to the third part of the water is 1 min to 2 min, and the stirring time after the triacetin is added is 5 min to 10 min; The sodium tripolyphosphate solution, the sodium aluminate solution, and the triacetin mixture are used for mixing the concrete within 10 to 30 minutes after preparation.
7. The modified preparation process according to claim 4, characterized in that, Before the dry mixing, the temperature of the ordinary silicate cement, the granulated blast furnace slag powder, the natural medium sand and the granite crushed stone is adjusted to 15℃~30℃, and the dry mixing time is 30s~60s; After the dry mixing is completed, the sodium tripolyphosphate solution is added and stirred for 30 to 60 seconds. The sodium aluminate solution is added within 20 to 40 seconds, and stirring is continued for 20 to 40 seconds. The triacetin mixture is then added within 20 to 40 seconds, and stirring is continued for 60 seconds. The total mixing time from the start of the dry mixing to the end of the wet mixing is 3 to 5 minutes. The operation of pouring the concrete into the conical steel mold is completed within 10 to 30 minutes after the concrete is mixed.
8. The modified preparation process according to claim 7, characterized in that, The centrifugal forming process includes, in sequence: Centrifuge at a centrifugal acceleration of 3g to 6g for 2 to 4 minutes; Centrifuge at a centrifugal acceleration of 10g to 18g for 3 to 5 minutes; Centrifuge at a centrifugal acceleration of 25g to 35g for 6 to 10 minutes; The mass of the residual slurry discharged during the centrifugal molding process accounts for 1% to 3% of the mass of the concrete poured into the conical steel mold; The average thickness of the continuous slurry-rich layer at the axial mid-section of the rod is 2 mm to 5 mm.
9. The modified preparation process according to claim 4, characterized in that, Before being fed into the steam curing kiln, the centrifuged conical steel mold is left to stand at 20℃~30℃ for 0.5h~1.5h. The measured maximum internal temperature of the rod was raised to 40℃~45℃ using a heating rate of 8℃ / h~12℃ / h, and then held at that temperature for 1.5h~2.5h. The highest measured temperature inside the rod is then raised to 58℃~62℃ using a heating rate of 10℃ / h~15℃ / h, and held for 4h~6h.
10. The modified preparation process according to claim 4, characterized in that, The cooling rate after the steam curing is completed is 8℃ / h to 15℃ / h; When the surface temperature of the rod is 35℃~45℃, the magnesium fluorosilicate aqueous solution is sprayed onto the inner wall of the rod. After the spraying is completed, seal both ends of the rod body and allow the magnesium fluorosilicate aqueous solution to react with the inner wall surface of the rod body under humid conditions for 30 to 60 minutes.
